The impact of positive childhood experiences: A systematic review focused on children and adolescents - Sousa, Marta (2025)
Childhood and adolescence are crucial stages of life, characterized by significant changes that profoundly influence overall development. While positive childhood experiences (PCEs) can help mitigate the effects of adverse events during these formative years, they have not been as thoroughly researched. Then, this systematic review aims to address this gap by organizing the existing literature on PCEs and examining their impact on both positive and negative outcomes in children and adolescents. A search through databases such as B-On, PsycINFO, PubMed, SCOPUS, and Scielo, as well as supplementary searches, identified 30 studies that met the inclusion criteria. The results indicate that most studies were published in the last 4 years, primarily in the USA, and focused on community populations with mixed samples. In addition, the results reveal that among children and adolescents, higher levels of PCEs were associated with better mental health outcomes (e.g., reduced depressive symptoms, anxiety, self-harm, substance use, and suicidal ideation), improved psychosocial outcomes (e.g., enhanced adult functioning and future orientation), better academic achievement (e.g., reduced absenteeism and fewer academic difficulties), and some improvements in physical health (e.g., reduced chronic pain). However, the relationship between PCEs and behavioral outcomes showed mixed results. Strengthening efforts to promote PCEs and resources that support child and adolescent resilience is crucial. Further research involving diverse samples is needed to gain a deeper understanding of the role of PCEs.